Watt-level 10-gigahertz solid-state laser enabled by self-defocusing nonlinearities in an aperiodically poled crystal. Issue 1 (December 2017) - Mayer, A.; Phillips, C.; Keller, U.
Abstract Femtosecond modelocked lasers with multi-gigahertz pulse repetition rates are attractive sources for all applications that require individually resolvable frequency comb lines or high sampling rates. However, the modelocked laser architectures demonstrated so far have several issues, including the need for single-mode pump lasers, limited output power, Q -switching instabilities and challenging cavity geometries. Here, we introduce a technique that solves these issues. In a two-dimensionally patterned quasi-phase-matching (QPM) device, we create a large, low-loss self-defocusing nonlinearity, which simultaneously provides SESAM-assisted soliton modelocking in the normal dispersion regime and suppressesQ -switching induced damage. We demonstrate femtosecond passive modelocking at 10-GHz pulse repetition rates from a simple straight laser cavity, directly pumped by a low-cost highly spatially multimode pump diode. The 10.6-GHz Yb:CaGdAlO4 (Yb:CALGO) laser delivers 166-fs pulses at 1.2 W of average output power. This enables a new class of femtosecond modelocked diode-pumped solid-state lasers with repetition rates at 10 GHz and beyond. Ultrafast lasers with multi-gigahertz repetition rates are desirable for applications requiring high sampling rates or resolvable frequency comb lines. Here, Mayer et al. use cascading of quadratic nonlinearities to passively modelock a femtosecond solid-state laser at a repetition rate of 10 GHz.